ANALISIS PERAN STAF PIUTANG DAN UTANG PADA PT X - Risandra, Marcelina Salsabila; Yuhertiana, Indrawati (STIE PENA, 2025)
This study explores the strategic role of Account Receivable (AR) and Account Payable (AP) staff in supporting financial management and operational continuity at PT X, an automotive service company. The research is motivated by the growing demand for efficiency and accuracy in managing corporate cash flow, particularly in a dynamic industry where receivables and payables are critical to financial stability. While many organizations have adopted digital systems for financial reporting, some still rely partly on manual processes, which can hinder timely decision-making and impact liquidity.Using a qualitative method through observation and structured interviews conducted during the author’s internship as part of the MBKM (Merdeka Belajar Kampus Merdeka) program, this study provides practical insights into how the AR and AP functions are implemented at PT X. On the AP side, although the transaction volume is relatively low—especially in disbursements related to training—its role remains essential in prioritizing vendor payments and sustaining operations. A key challenge in managing accounts payable lies in the grouping of payment requests, which requires effective scheduling and coordination.The study concludes that AR and AP staff are not merely administrative personnel, but key players in managing cash flow, strengthening vendor-client relationships, and ensuring financial control. This research contributes to a deeper understanding of financial operations by emphasizing the importance of timely data entry, digital system integration, and interdepartmental collaboration. It also offers practical recommendations for PT X, including the adoption of ERP-based reporting tools, regular staff training in financial systems, and structured payment scheduling. Future research is encouraged to apply a quantitative approach to assess the broader impact of AR/AP management on financial ratios and long-term performance. Keywords: Receivable, Payable, Cash Flow